Pelanggaran Inviolability Pada Diplomatic Bag Dalam Kasus Pembukaan Diplomatic Bags China Oleh Amerika Serikat, Beijing Berang - Rai Yuliartini, Ni Putu; Trisna Yuliartini, Ni Luh Putu (Jurnal Komunikasi Hukum, 2021)
The freedom and confidentiality of communication between diplomatic missions and sending countries is the most important privilege and immunity in diplomatic relations. The diplomatic bag is one of the many communication facilities excluded from Article 27 of the 1961 Vienna Convention on Diplomatic Relations. The form of immunity is the prohibition of the opening and detention of diplomatic bags. The existence of these exceptions often raises problems, either caused by the actions of the receiving country and / or third country and sending country. The study aims to analyze the possibility of providing "inviolability" based on the source and purpose of diplomatic pockets and the state's responsibility for the abuse of diplomats in diplomatic bag. This diplomatic bag is one of the triggers for the fracture of bilateral relations between countries that have worked together for a period of time, for example, the United States and China. The unauthoided opening of China's diplomatic pockets by the United States in 2018 and 2020 has twice led China and the United States to issue retaliatory action.